Two-Dimensional Materials Applied to Hydrogen Storage - Martins, Nicolas F. [UNESP]; Laranjeira, José A. S. [UNESP]; Azevedo, Sergio A.; Fabris, Guilherme S. L.; Denis, Pablo A.; Sambrano, Julio R. [UNESP] (Springer Nature, 2024)
Hydrogen as a clean and efficient energy has received much attention due to its potential to address global energy challenges. However, efficient storage methods continue to be a critical bottleneck and, therefore, a challenge for the scientific community. In this sense, several material classes have been proposed as possible candidates for this finding. Among them, two-dimensional (2D) materials have emerged as promising candidates for hydrogen storage due to their unique properties, including high surface area, tunable electronic properties, and chemical stability. In this chapter, the recent advancements in 2D materials for hydrogen storage were highlighted. Hydrogen adsorption mechanisms on 2D materials and their performance, such as gravimetric and volumetric hydrogen storage capacities, kinetics, and reversibility, were emphasized. The analysis and design of efficient devices to store H2 are validated through computational simulations and available experimental data, which enables a comprehensive analysis of hydrogen storage on 2D materials.
Keywords: 2D materials; Graphene; H2; Mxene; TMD